Effects of Hexamethyldisilazane Modification on Gas-Sensing Properties of Semiconductor Gas Sensors. (8th September 2020) - Ueda, Taro; Fukuura, Hiroto; Kamada, Kai; Hyodo, Takeo; Shimizu, Yasuhiro
Abstract : SnO2 -based sensors were modified with hexamethyldisilazane (HMDS), and their sensing properties to CH4 and H2 were examined. The HMDS modification decreased the CH4 response and increased the H2 response of all the sensors tested. In addition, the response time of all the sensors to H2 remained unchanged by the HMDS modification, even though their response time to CH4 and their recovery times to both CH4 and H2 tended to become long with an increase in the amount of HMDS modified. The XPS analyses suggested that the formation of a SiO2 thin layer on the surface of SnO2 by the HMDS modification. The existence of the SiO2 thin layer moderately decreased the amount of negatively charged oxygen adsorbates on the SnO2 surface, and drastically restricted the diffusion of large-sized gases, CH4 and O2, to the SnO2 surface. They are possible reasons why the HMDS modification enhanced the H2 response of the sensors.